Desain Lintasan Belajar Matematika dalam Pembelajaran Arimatika Sosial Menggunakan Aplikasi Quizlet untuk Meningkatkan Pemahaman Konsep - Laswadi Laswadi (Departement of Mathematics Education, 2023)
Conceptual understanding is a crucial skill in learning mathematics, especially in the context of concepts relevant to students' everyday lives, such as Social Arithmetic. However, students often face difficulties in gaining a deep understanding of mathematical concepts. This study aims to test the implementation of the Quizlet application in mathematics learning to enhance students' conceptual understanding. The Design Research method is employed in this study, involving stages such as preliminary design, design experimentation, and retrospective analysis to design an effective learning path. The results of the study indicate a significant positive influence of using the Quizlet application on students' conceptual understanding of mathematics. This research suggests that the application has the potential to serve as an effective tool to facilitate enjoyable and easy mathematics learning for students.